Christianity and Modern Medicine: Foundations for Bioethics - Just, Bryan R. (Trinity journal, 2023)
Review of Foreman, Mark W (Mark Wesley). Christianity and Modern Medicine: Foundations for Bioethics. Publisher: Grand Rapids : Kregel Academic, 2022. ISBN: 978-0-8254-4756-3.